ANGIOMYOLIPOMA OF THE KIDNEY - Muhammad, Gul; zeb, Aurang; Sultan, Shahid (Journal of Ayub Medical College Abbottabad, 1988)
The angiomyolipoma is an unusual tumour, composed of mature adipose tissue, blood vessels and smooth muscle with supporting stroma. It is generally regarded as benign-hamartoma. Such tumour may grow to a large size. There is a well-recognized association between angiomyolipoma and tuberous sclerosis. In such cases tumours are invariably multiple and frequently bilateral. They may enlarge to produce palpable renal masses. This may also be found in patients lacking the stigmata of tuberous sclerosis complex. Inglis (1960) and Price and Mostofi (1965) gave an excellent resume of condition in 30 patients free from tuberous sclerosis. The commonest presenting symptoms are loin pain and renal mass.